2020
DOI: 10.3390/ijms21072298
|View full text |Cite
|
Sign up to set email alerts
|

Regulative Loop between β-catenin and Protein Tyrosine Receptor Type γ in Chronic Myeloid Leukemia

Abstract: Protein tyrosine phosphatase receptor type γ (PTPRG) is a tumor suppressor gene, down-regulated in Chronic Myeloid Leukemia (CML) cells by the hypermethylation of its promoter region. β-catenin (CTNNB1) is a critical regulator of Leukemic Stem Cells (LSC) maintenance and CML proliferation. This study aims to demonstrate the antagonistic regulation between β-catenin and PTPRG in CML cells. The specific inhibition of PTPRG increases the activation state of BCR-ABL1 and modulates the expression of the BCR-ABL1- d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Exposure to ionizing radiation is the only known risk factor for CML [4]. Tyrosine kinase inhibitors are a cornerstone in the management of CML around the world with good results [5][6][7][8][9]. This case is shedding light on a possible association between TB and the development of CML.…”
Section: Introductionmentioning
confidence: 94%
“…Exposure to ionizing radiation is the only known risk factor for CML [4]. Tyrosine kinase inhibitors are a cornerstone in the management of CML around the world with good results [5][6][7][8][9]. This case is shedding light on a possible association between TB and the development of CML.…”
Section: Introductionmentioning
confidence: 94%
“…Consistently, over-expression of LEF-1 mRNA is a hallmark in ALL and CLL patients with poor prognostic. The constitutive activation of the pathway deregulation can result from gene mutation ( Tomasello et al, 2020 ), but also from epigenetic modifications. In CLL for example, Next generation sequencing of samples from patients confirmed that 40% of patients harbors somatic mutations in Wnt pathway components ( WNT1 , WNT10A , DKK2 , RSPO4, FZD5, RYK ) ( Wang et al, 2014 ).…”
Section: Msc-derived Notch and Wnt Signaling In Leukemiamentioning
confidence: 99%
“…Concerning myeloid malignancies, Zhao et al found that β-catenin deletion causes a reduction in the ability of mice to develop BCR-ABL-induced CML ( Zhao et al, 2007 ). Indeed, stabilization and nuclear localization of β-catenin is a direct consequence of the BCR-ABL ( Tomasello et al, 2020 ). As a consequence, the treatment of CML stem/progenitor cells with β-catenin inhibitor ICG001 reduces cell survival and proliferation by sensitizing cells to tyrosine kinase inhibitors (TKI).…”
Section: Msc-derived Notch and Wnt Signaling In Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation of BCR-ABL1 prevents complete β-catenin phosphorylation, with consequent destabilization and proteasome degradation. In addition, PTPRG seems to directly dephosphorylate β-catenin, providing further details on its tumor-suppressive effects in CML [ 118 ]. Methylation play an extremely important role in the regulation of PTPRG expression in CML—a feature shared with other malignancies [ 119 ].…”
Section: Role Of Phosphatases In Chronic Myeloid Leukemiamentioning
confidence: 99%